Evaluation of the impact of immediate versus WHO recommendations-guided antiretroviral therapy initiation on HIV incidence: the ANRS 12249 TasP (Treatment as Prevention) trial in Hlabisa sub-district, KwaZulu-Natal, South Africa: study protocol for a cluster randomised controlled trial - Iwuji, Collins C.; Tanser, Frank; Bärnighausen, Till; Newell, Marie-Louise (Trials, 2013)
Antiretroviral therapy (ART) suppresses HIV viral load in all body compartments and so limits the risk of HIV transmission. It has been suggested that ART not only contributes to preventing transmission at individual but potentially also at population level. This trial aims to evaluate the effect of ART initiated immediately after identification/diagnosis of HIV-infected individuals, regardless of CD4 count, on HIV incidence in the surrounding population. The primary outcome of the overall trial will be HIV incidence over two years. Secondary outcomes will include i) socio-behavioural outcomes (acceptability of repeat HIV counselling and testing, treatment acceptance and linkage to care, sexual partnerships and quality of life); ii) clinical outcomes (mortality and morbidity, retention into care, adherence to ART, virologic failure and acquired HIV drug resistance), iii) cost-effectiveness of the intervention. The first phase will specifically focus on the trial’s secondary outcomes.
Gesehen am 18.01.2018